2006
DOI: 10.1007/11780441_12
|View full text |Cite
|
Sign up to set email alerts
|

Tiling an Interval of the Discrete Line

Abstract: Abstract. We consider the problem of tiling a segment {0, . . . , n} of the discrete line. More precisely, we ought to characterize the structure of the patterns that tile a segment and their number. A pattern is a subset of N. A tiling pattern or tile for {0, . . . , n} is a subset A ∈ P(N) such that there exists B ∈ P(N) and such that the direct sum of A and B equals {0, . . . , n}. This problem is related to the difficult question of the decomposition in direct sums of the torus Z/nZ (proposed by Minkowski)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In particular we get a recursive formula for computing function L(n) that gives the maximal number of tiling periods for a unary word of length n. The value L(n) might be even more than the text length. Actually, Bodini and Rivals obtain this recursive formula a few months earlier: their paper [3] was submitted in January 2006, while our results were reported only in May 2006 [10]. Here we keep our proof since (comparing to [3]) it construct explicit one-to-one correspondence between tilers and length factorizations, and introduces levels in the set of all tilers.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…In particular we get a recursive formula for computing function L(n) that gives the maximal number of tiling periods for a unary word of length n. The value L(n) might be even more than the text length. Actually, Bodini and Rivals obtain this recursive formula a few months earlier: their paper [3] was submitted in January 2006, while our results were reported only in May 2006 [10]. Here we keep our proof since (comparing to [3]) it construct explicit one-to-one correspondence between tilers and length factorizations, and introduces levels in the set of all tilers.…”
Section: Introductionmentioning
confidence: 80%
“…Actually, Bodini and Rivals obtain this recursive formula a few months earlier: their paper [3] was submitted in January 2006, while our results were reported only in May 2006 [10]. Here we keep our proof since (comparing to [3]) it construct explicit one-to-one correspondence between tilers and length factorizations, and introduces levels in the set of all tilers.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…A list of the first 1000 elements of the sequence (F(n)) n≥1 can be found on the OnLine Encyclopedia of Integer Sequences (A067824) [8]. Bodini and Rivals [2] showed that F(n) is equal to the number of polynomials over x, p(x), with coefficients in the set {0, 1} such that ( ) ( ) also has coefficients in the set {0, 1}.…”
Section: Counting Full and Partial Tilings Over A Unary Alphabetmentioning
confidence: 99%
“…More recent examples of a Minkowski representation include three-dimensional modeling of prosthetic teeth [19], onedimensional tiling of discrete lines [3], two-dimensional packing of polygons of dissimilar shapes [6], and laying out of shapes on a fabric or material with specific orientation constraints and tolerances [12,8]. The most relevant of these to the current work are those working in two dimensions, as this paper's problem is a twodimensional layout problem.…”
Section: Introductionmentioning
confidence: 98%